Benefits and Costs of Brain and Ability Drain - Maurice Schiff (Institute of Labor Economics (IZA), 2024)
Ability drain's (AD) impact on host countries is significant: 30 percent of US Nobel laureates since 1906 are immigrants, and they or their children founded 40 percent of Fortune 500 companies. However, while brain drain (BD) and gain (BG) have been studied extensively, AD has not. I examine migration's impact on ability (a), education (h), and productive human capital s = s(a, ℎ), for home country residents and migrants under the 'vetting' immigration system, which accounts for s (e.g., US H-1B program). Findings are: i) Education increases with ability; ii) Migration reduces (raises) residents' (migrants') average ability, with an ambiguous (positive) impact on the average level of ℎ and s; iii) These effects increase with ability's inequality or variance; iv) The model and empirical studies suggest that AD ≥ BD for educated US immigrants and that their real income is about twice their home country income; v) A net drain in average s holds for any BD and for an AD that is a fraction of our estimate; vi) This article also provides a detailed description of the multiple home country benefits generated by the brain and ability drains. And policy implications are presented.
Keywords: F22; J24; J61; O15; 330; migration; points system; vetting system; ability drain; brain drain; brain gain